2023
DOI: 10.3390/oxygen3030020
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Driven Responses in Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) affects 10% of the population. Fibrosis is the hallmark of CKD, which is marked by the deposit of extracellular matrix (ECM). This response is the final outcome of an unbalanced reaction to inflammation and wound healing and can be induced by a variety of insults, including hypoxia. Vascular damage results in an impaired tissue oxygen supply, inducing immune cell infiltration, tubule injury and the activation of ECM-secreting myofibroblasts. In turn, tubulointerstitial fibrosis dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 211 publications
1
2
0
Order By: Relevance
“…A recent study has demonstrated that hypoxia, characterized by low cellular oxygen concentrations, activates APOL1 transcription in kidney podocytes and tubular cells [ 38 ]. This finding aligns with the known role of renal hypoxia in kidney injury and repair and the pathogenesis of CKD and ESRD [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. The innate vulnerability of kidneys to hypoxia is attributed to their vascular structure and high-energy-demanding functions [ 47 ].…”
Section: Introductionsupporting
confidence: 87%
“…A recent study has demonstrated that hypoxia, characterized by low cellular oxygen concentrations, activates APOL1 transcription in kidney podocytes and tubular cells [ 38 ]. This finding aligns with the known role of renal hypoxia in kidney injury and repair and the pathogenesis of CKD and ESRD [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. The innate vulnerability of kidneys to hypoxia is attributed to their vascular structure and high-energy-demanding functions [ 47 ].…”
Section: Introductionsupporting
confidence: 87%
“…A lack of oxygen usually induces anaerobic metabolism in the cells; however, in some parts of the kidney, such as proximal tubules, this metabolic pathway is unable to meet the high energy demands of the kidneys. Moreover, a lack of ATP interrupts normal Na + , Ca 2+ , and K + transport through the cellular membrane, which leads to calcium overload, the generation of reactive oxygen species, and the opening of mitochondrial permeability transition pores after reoxygenation or reperfusion, all of which leads to the loss of tubular epithelial cells [ 4 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with CKD develop hypoxia due to increased incidence of cardiovascular diseases, reducing the supply of oxygen to the tissues. Additional factors of tissue hypoxia include anemia, hyperglycemia, hypertension, smoking, hypercholesterolemia, and atherosclerosis [ 13 ]. Under hypoxic conditions, the elements contribute to the initiation of the apoptosis pathway, fibroblast and leukocyte activation, and subsequent extracellular matrix deposition (ECM).…”
Section: Introductionmentioning
confidence: 99%